2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944438
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of signal use and vehicle turns as indication of driver cognition

Abstract: This paper uses data analytics to provide a method for the measurement of a key driving task, turn signal usage as a measure of an automatic over-learned cognitive function drivers. The paper augments previously reported more complex executive function cognition measures by proposing an algorithm that analyzes dashboard video to detect turn indicator use with 100% accuracy without any false positives. The paper proposes two algorithms that determine the actual turns made on a trip. The first through analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Driving is a very complex cognitive task including executive function tasks such as trip and route planning through to highly trained and learned tasks such as turn signal use. The measurement of driving is presented in three sections with an initial focus of measurement of driving behaviours that are unique to the driver, the measurement of navigational performance as an indication of cognitive ability and the measurement of turn signal use as one measure of vehicle operation (refereed journals [10] and conferences [12][13][14][15][16][17][18][19][20][21]).…”
Section: Driving Cognition Measurementmentioning
confidence: 99%
“…Driving is a very complex cognitive task including executive function tasks such as trip and route planning through to highly trained and learned tasks such as turn signal use. The measurement of driving is presented in three sections with an initial focus of measurement of driving behaviours that are unique to the driver, the measurement of navigational performance as an indication of cognitive ability and the measurement of turn signal use as one measure of vehicle operation (refereed journals [10] and conferences [12][13][14][15][16][17][18][19][20][21]).…”
Section: Driving Cognition Measurementmentioning
confidence: 99%
“…Gyllensten et al, however, have shown that these accuracies can be misleading, as movements in the real world are rarely as clearly defined as they are in the laboratory setting [58]. [64]. These studies have shown that sensor equipment is capable of providing a clearer understanding of drivers'…”
Section: Accelerometer Calibrationmentioning
confidence: 99%
“…as changes in heading of 70 o to 110 o across the entire event (i.e., total change in heading from the start to end of the event). Wallace et al [56] identified when the vehicle was turning using only the GPS data from a smartphone GPS sensor and the proposed turnidentification algorithm was based on the change in heading of 30 o between sampled GPS coordinates; their performance was 73% true positive rate, 3% false positive rate, and 14% false negative rate tested on 215 true turns. In the same study, the turn-identification algorithm was compared to using the Google Maps GIS algorithm for identifying turns.…”
Section: Turn Identificationmentioning
confidence: 99%
“…The three turn-identification algorithms involved locating the coordinates that occur within a turn, and then locating the start and the end of the turns. The first algorithm was based on a threshold on the change in heading to find significant corners and bends, and this algorithm was implemented by Wallace et al [56] for counting the number of turns in a trip. The second algorithm was an extension of the first algorithm by simplifying the GPS trace before applying a threshold on the change in heading to emphasize the corners.…”
Section: Turn-identification Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation